Qhatuyki Store modelo de negocio para pequeños distritos urbanos - García Bustinza, Daniel Israel (2020)
Qhatuyki Store, is the composition of the word Qhatu (Quechua of Cusco that translated into Spanish means market) with the second-person possessive suffix yki (Your Market) and the English word Store, that in the context of the Internet it is directly associated with an e-commerce or electronic commerce establishment. What Qhatuyki Store offers to the user, bilingual in a significant percentage and with strong Quechua self-identification, is the concept of a virtual market, with online stores, located in their city. That is, "your digital market to buy and sell in your own small town", through a technological platform, which allows associating small commercial establishments (many times not considered by digital entrepreneurship such as small stores, pharmacies, bazaar stores, grocery stores, etc.) with delivery carriers; to be able to offer their consumers the experience of online shopping and delivery express service, without the need to have a credit card or a bank account to make their payments. Buyer users will be able to purchase the products they need in their favorite trusted stores in their own city and receive them in the comfort of their home, work or wherever they want, in the shortest possible time.